Soil water availability and rooting depth as determinants of hydraulic architecture of Patagonian woody species - Bucci, Sandra Janet (2009)
Adaptations of species to capture limiting resources is central for understanding structure and function of ecosystems. We studied the water economy of nine woody species differing in rooting depth in a Patagonian shrub steppe from southern Argentina to understand how soil water availability and rooting depth determine their hydraulic architecture. Soil water content and potentials, leaf water potentials (ΨLeaf), hydraulic conductivity, wood density (ρw), rooting depth, and specific leaf area (SLA) were measured during two summers. Water potentials in the upper soil layers during a summer drought ranged from -2.3 to -3.6 MPa, increasing to -0.05 MPa below 150 cm. Predawn ΨLeaf was used as a surrogate of weighted mean soil water potential because no statistical differences in ΨLeaf were observed between exposed and covered leaves. Species-specific differences in predawn ΨLeaf were consistent with rooting depths. Predawn ΨLeaf ranged from -4.0 MPa for shallow rooted shrubs to -1.0 MPa for deep-rooted shrubs, suggesting that the roots of the latter have access to abundant moisture, whereas shallow-rooted shrubs are adapted to use water deposited mainly by small rainfall events. Wood density was a good predictor of hydraulic conductivity and SLA. Overall, we found that shallow rooted species had efficient water transport in terms of high specific and leaf specific hydraulic conductivity, low ρw, high SLA and a low minimum ΨLeaf that exhibited strong seasonal changes, whereas deeply rooted shrubs maintained similar minimum ΨLeaf throughout the year, had stems with high ρw and low hydraulic conductivity and leaves with low SLA. These two hydraulic syndromes were the extremes of a continuum with several species occupying different portions of a gradient in hydraulic characteristics. It appears that the marginal cost of having an extensive root system (e.g., high ρw and root hydraulic resistance) contributes to low growth rates of the deeply rooted species.